Assessment of pesticide residues in vegetables produced in central and eastern Ethiopia - Getachew Dinede; Wubetu Bihon; Lina Gazu; Serge Foukmeniok Mbokou; Sisay Girma; Ramasamy Srinivasan; Ralph Roothaert; Delia Grace; Delia Grace; Habtamu Gashaw; Theodore J. D. Knight-Jones (Frontiers in Sustainable Food Systems, 2023)
BackgroundIn Ethiopia, pesticides are widely used in vegetable production. However, if used incorrectly they may harm consumers of vegetables contaminated with pesticide residues, as well as producers handling the pesticides and lead to ecological damage. We performed a cross-sectional survey to assess pesticide residues in vegetables produced in central and eastern Ethiopia.MethodsA total of 232 vegetable samples (91 tomatoes, 106 cabbages and 35 Swiss chard) were collected from fields and retail markets, and were screened for 35 pesticides (16 organochlorine, 11 organophosphate, 3 pyrethroids, 2 carbamates and 3 other agrochemicals) using GC–MS analysis.ResultsPesticides residues were detected in 60% of Swiss chard, 47% of cabbage and 45% of tomato samples. Two or more pesticides were detected in 20% of cabbages, 13% of tomatoes and over half of Swiss chard samples. Bendiocarb, diazinon, endrin, piperonyl butoxide, profenofos and propargite were detected, but only diazinon, propargite and profenofos had residual values above EU Maximum Residue Level (MRL), with diazinon commonly detected at relatively high levels. About 15% of the total analyzed samples, 10% of cabbages and tomatoes, and nearly half of Swiss chard samples had pesticide concentration exceeding EU MRL. However, none of the tested samples had residues exceeding Codex Alimentarius Commission (Codex) MRLs.ConclusionThis study showed widespread contamination of vegetables with pesticides, mainly organophosphates. We recommend monitoring and regulation of pesticides usage, with promotion of good agricultural practices.